Carbonized wood loaded high-entropy phosphide nanosheet composite electrocatalyst and preparation method thereof

By constructing a high-entropy phosphide nanosheet composite electrocatalyst in situ on carbonized wood, the problem of poor stability of existing electrocatalysts under high current density is solved, and an efficient and low-cost electrochemical water decomposition hydrogen production effect is achieved.

CN119913544APending Publication Date: 2025-05-02SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077367.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing electrocatalysts have problems of high cost, low efficiency and poor stability in electrochemical water decomposition, especially at high current density, which makes it difficult to meet the requirements of stable operation.

Method used

Carbonized wood is used as a scaffold to construct a composite electrocatalyst of high entropy phosphide nanosheets in situ through hydrothermal reaction and one-step phosphating method. The three-dimensional porous structure of carbonized wood and a multi-element system of high entropy phosphide are used to improve the activity and stability of the catalyst.

Benefits of technology

It significantly reduces the applied potential required for electrolyzing water, improves the efficiency of electrolyzing water to prepare high-purity hydrogen, and improves the performance of electrocatalytic coupling of glucose hydrogen production, which is better than traditional electrocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913544A_ABST
    Figure CN119913544A_ABST
Patent Text Reader

Abstract

The invention discloses a carbonized wood loaded high-entropy phosphide nanosheet composite electrocatalyst and a preparation method thereof.The method comprises the steps that deionized water serves as a solvent, hexamethylenetetramine is added into a mixed system of Ni (NO3) 26H2O, citric acid, FeCl3, Co (NO3) 2.6 H2O, Na2WO4. 2H2O and Na2MoO4. 2H2O to be evenly mixed, and the mixed system is obtained; carbonized wood is immersed in the mixed system and then subjected to a hydrothermal reaction at the temperature of 140-180 DEG C, an obtained product is washed and dried, and a carbonized wood loaded high-entropy phosphide nanosheet precursor is obtained; the carbonized wood loaded high-entropy phosphide nanosheet precursor and a phosphorus source are subjected to one-step phosphorization at the temperature of 300-600 DEG C, the carbonized wood loaded high-entropy phosphide nanosheet composite electrocatalyst is obtained, the external potential needed by water electrolysis is reduced, and the efficiency of preparing high-purity hydrogen through water electrolysis is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalyst preparation, and specifically relates to a carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst and a preparation method thereof. Background Art

[0002] Electrochemical water splitting to produce hydrogen is an emerging sustainable energy conversion and storage technology with the characteristics of sustainability, zero carbon emissions and high energy density. It has great potential in solving serious energy crises and environmental problems, and has therefore attracted widespread attention. However, the further development of this technology is hindered by the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), which require the use of high-cost and scarce precious metals as electrocatalysts (such as Pt, IrO 2 , and RuO 2 ) to reduce the reaction energy consumption. In particular, OER is a four-electron coupled transfer process with high working voltage and low energy efficiency. Therefore, replacing OER with more cost-effective and thermodynamically advantageous electrocatalytic organic matter conversion (alcohols, ureas, hydrazine, ammonia and furfural, etc.) is a potential way to produce hydrogen, which not only has the advantages of low energy consumption but also can produce high value-added products. Among these organic electrocatalytic conversion reactions, glucose is a biomass monosaccharide that is widely present in nature and has a low redox potential. It can be selectively converted into formate and has a wide range of applications in agriculture, pharmaceuticals, rubber, leather, textile and food industries. However, glucose is a polyhydroxy aldehyde structure, and its electrocatalytic conversion involves a complex reaction path and a multi-step electron-coupled proton transfer process, which greatly reduces the selectivity of formate. Therefore, it is imperative to develop electrocatalysts with high catalytic selectivity for the electrocatalytic conversion of glucose.

[0003] Among these electrocatalysts, high entropy materials (HEMs), including high entropy alloys (HEAs), oxides, layered double hydroxides (LDHs), phosphides, sulfides, etc., are considered to be an emerging class of electrocatalysts, usually composed of five or more elements with similar contents. Compared with single, binary or ternary metal compounds, phosphides, especially high entropy phosphides (HEPs), have slow diffusion effects, accommodating electronic structures, entropy stability and cocktail effects. The large composition space of HEPs makes them exhibit rich and diverse active sites, resulting in heterogeneous adsorption of reaction substrates and intermediates, making them suitable for multi-electron coupled proton transfer processes for complex biomass electrocatalytic conversion. In particular, making full use of heterogeneous adsorption to achieve adsorption activation of reaction substrates, diffusion of intermediates and desorption of products not only accelerates the reaction efficiency but also improves the selectivity of products.

[0004] However, HEPs still face problems such as easy shedding of nanomaterials, poor accessibility of active sites, slow electron transfer, and poor mass transfer during electrocatalysis. Especially at high current density, the electrolyte is not wetted enough, and bubbles overflow and block the channel. Therefore, the ideal HEPs electrocatalyst should be low-cost, self-sufficient, good activity and remarkable stability, while having abundant active sites, fast wettability, excellent mass transfer and charge transfer, and can meet the requirements of stable operation at high current density to the greatest extent. Natural wood is renewable, abundant, low-cost and sustainable. In recent years, wood-derived porous carbon-based electrocatalysts have received extensive attention, especially carbonized wood (CW), which well retains the characteristics of low-curvature microchannels and its nano-, micro- and macro-hierarchical structures. Therefore, it is necessary to develop a high-entropy phosphide electrocatalyst with high hydrogen production efficiency using carbonized wood as a scaffold to in situ construct low-curvature microchannels and three-dimensional hierarchical porous structures. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst and a preparation method, and in situ constructs a high-entropy phosphide electrocatalyst with high hydrogen production efficiency using carbonized wood as a support, having low-curvature microchannels and a three-dimensional layered porous structure, which reduces the external potential required for water electrolysis and improves the efficiency of preparing high-purity hydrogen by water electrolysis.

[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst comprises the following steps: S1, using deionized water as solvent, in Ni(NO 3 ) 2 ⋅6H 2 O, citric acid, FeCl 3 、Co(NO 3 ) 2 6H 2 O、Na 2 WO 4 ·2H 2 O and Na 2 MoO 4 ·2H 2 O mixed system, add hexamethylenetetramine and mix well, Ni(NO 3 ) 2 ⋅6H 2 O、Co(NO 3 ) 2 6H 2 O、Na 2 WO 4 ·2H 2 O, FeCl3 and Na 2 MoO 4 ·2H 2 The molar ratio of the total amount of O to citric acid is 1:1, and a mixed system is obtained; S2, immerse the carbonized wood into the mixed system and heat it at 140~180 o C, and the obtained product is washed and dried to obtain a carbonized wood-supported high-entropy phosphide nanosheet precursor; S3, carbonized wood-supported high entropy phosphide nanosheet precursor and phosphorus source were heated to 300-600 o C, the ratio of phosphorus source to citric acid in S1 was (0.5~1.5) g: 5 mmol, and the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst was obtained.

[0007] Preferably, S1 first converts Ni(NO 3 ) 2 ⋅6H 2 O, FeCl 3 、Co(NO 3 ) 2 6H 2 O and citric acid are dissolved in a mixed solvent of deionized water and anhydrous ethanol in sequence to obtain solution A; Will Na 2 WO 4 ·2H 2 O and Na 2 MoO 4 ·2H 2 O is dissolved in deionized water to obtain solution B; Solution B was added to solution A and magnetically stirred for 15 to 25 min, and then hexamethylenetetramine was added to obtain a mixed system.

[0008] Preferably, Ni(NO 3 ) 2 ⋅6H 2 O, FeCl 3 、Co(NO 3 ) 2 6H 2 O、Na 2 WO 4 ·2H 2 O and Na 2 MoO 4 ·2H 2 The molar ratio of O is (0.25~4):(0.25~4):(0.25~4):(0.25~4):(0.25~4), the molar ratio of hexamethylenetetramine to citric acid is 8:5, and the volume ratio of deionized water and anhydrous ethanol in solution A is 1:1.

[0009] Preferably, the carbonized wood described in S2 is obtained by the following process: The wood pieces were soaked in 0.85-1.15 M hydrochloric acid for 55-65 min, washed with deionized water and anhydrous ethanol, and dried. o The first carbonization was carried out at 0.5-2 h under 400 °C and finally heated to 800-1000 °C in an oxygen-free atmosphere. o C and then carbonized for a second time for 2-4 h to obtain carbonized wood.

[0010] Preferably, the heating rate during the first carbonization is 1 to 3 o C min -1 The heating rate during the second carbonization is 3~6 o C min -1 .

[0011] Preferably, S2 immerses the carbonized wood into the mixed system at 140-180 o C for 8 to 16 h.

[0012] Preferably, S2 washes the product with water and ethanol in sequence at 55-65 o C and vacuum dried for 12 to 18 h to obtain a carbonized wood-supported high entropy phosphide nanosheet precursor.

[0013] Preferably, the phosphorus source in S3 is NaH 2 PO 2 ⋅H 2 O, S3 carbonized wood-supported high entropy phosphide nanosheet precursor and NaH 2 PO 2 ⋅H 2 O were placed in the downstream and upstream of the tube furnace, and then o C for 1-3 h to obtain the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst.

[0014] Preferably, S3 is 2 to 4 o C min -1 The heating rate of carbonized wood-supported high entropy phosphide nanosheet precursor and NaH 2 PO 2 ⋅H 2 O is heated from room temperature to 300~600 o C, and then keep warm at the above temperature.

[0015] A carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst obtained by the preparation method of the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst described in any one of the above.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which uses carbonized wood as a substrate, hexamethylenetetramine as a reducing agent, and citric acid as a complexing agent, and controls Ni(NO 3 ) 2 ⋅6H 2 O、Co(NO 3 ) 2 6H 2 O、Na 2 WO 4 ·2H 2 O, FeCl 3 and Na 2 MoO 4 ·2H 2 The molar ratio of the total amount of O to citric acid and the reaction temperature were used to in situ grow the high entropy phosphide nanosheet precursor on the carbonized wood. 2 PO 2 ·H 2 O is the phosphorus source. By adjusting the ratio of phosphorus source and the total amount of metal elements, the carbonized wood-loaded high-entropy phosphide nanosheet electrocatalyst is prepared by a one-step phosphating method, which significantly improves the HER, OER and glucose electrocatalytic assisted water electrolysis hydrogen production performance of the catalyst. The three-net porous structure of carbonized wood effectively ensures the uniform distribution of high-entropy phosphide nanosheets, providing abundant active sites for the catalyst. The electronegativity and radius differences of each element in the multi-element system of high-entropy phosphide induce changes in the overall electronic structure. The coexistence of multiple elements shows a variety of active sites, which further improves the efficiency of the catalyst's biomass electrocatalytic conversion coupled hydrogen production.

[0017] Furthermore, the present invention can remove impurities from the flaky wood by soaking it in 0.85-1.15 M hydrochloric acid, and use natural flaky wood as a substrate. By reasonably controlling the temperature and time of the two-step carbonization, carbonized wood with excellent conductivity and a large specific surface area is obtained, and the structural characteristics of the low-curvature microchannel of natural wood are retained. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1a This is a SEM image of the radial section of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0019] Figure 1b This is a SEM image of the cross-section of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0020] Figure 1cThis is a high-resolution SEM image of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0021] Figure 2 This is the X-ray diffraction spectrum of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0022] Figure 3 This is the Raman spectrum of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0023] Figure 4 This is the nitrogen adsorption-desorption curve of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0024] Figure 5 This is the full XPS spectrum of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0025] Figure 6 This is a performance diagram of the hydrogen evolution polarization curve of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0026] Figure 7 This is a performance diagram of the oxygen evolution polarization curve of the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst obtained in Example 2.

[0027] Figure 8 This is a performance diagram of polarization curves of water electrolysis and glucose electrocatalytic conversion assisted water electrolysis using the carbonized wood-loaded high entropy phosphide nanosheet composite electrocatalyst obtained in Example 2. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0029] The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h, and finally at 200-300 o C for 0.5~2 h, and the heating rate is 1~3 o C min -1 , and then heated to 800~1000 in a nitrogen atmosphere. o C carbonization 2~4 h, heating rate 3~6 o C min -1, obtaining carbonized wood (CW); Step 2: 0.25~4 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 0.25~4 mmol FeCl 3 , 0.25~4 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 0.25-4 mmol Na 2 WO 4 ·2H 2 O and 0.25~4 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water. The total amount of each metal ion was 5 mmol, which could be 1, 1, 1, 1, 1 mmol or 2, 0.5, 0.5, 1, 1 mmol, respectively. The mixture was stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and stirred magnetically for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and stirred magnetically for 20 minutes. The mixture was transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 140-180 °C. o After cooling to room temperature, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0030] Step 3: Mix the NiFeCoWMo / CW obtained above with 0.5-1.5 g of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1 The tube furnace is heated from room temperature to 300~600 o C, and keep warm for 1-3 hours. The tube furnace is cooled to room temperature to obtain NiFeCoWMoP / CW.

[0031] Example 1 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 300 o C for 0.5 h, and the heating rate was 1 o C min -1 , and then heated to 1000 o C carbonization for 4 h, heating rate of 3 o C min -1 , obtaining carbonized wood (CW); Step 2: 0.5 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 1 mmol FeCl 3 , 1 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 0.5 mmol Na 2 WO 4 ·2H 2 O and 2 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was then transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 140 o After cooling to room temperature naturally, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0032] Step 3: Mix the NiFeCoWMo / CW obtained above with 0.5 g of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1 The tube furnace is heated from room temperature to 600 o C, and keep it warm for 3 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0033] Example 2 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 260 o C for 0.5 h, with a heating rate of 3 o C min -1 , and then heated to 800 o C carbonization for 3 h, heating rate 5 o C min -1 , obtaining carbonized wood (CW); Step 2: 1 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 1 mmol FeCl 3 , 1 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 1 mmol Na 2 WO 4 ·2H 2 O and 1 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was then transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 160 o After cooling to room temperature, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0034] Step 3: Mix the NiFeCoWMo / CW obtained above with 1 g of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1The tube furnace was heated from room temperature to 450 o C, and keep it warm for 3 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0035] Example 3 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 200 o C for 2 h, with a heating rate of 3 o C min -1 , and then heated to 1000 o C carbonization for 4 h, heating rate 5 o C min -1 , obtaining carbonized wood (CW); Step 2: 3 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 0.5 mmol FeCl 3 , 0.5 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 0.5 mmol Na 2 WO 4 ·2H 2 O and 0.5 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was then transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 160 o After cooling to room temperature, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0036] Step 3: Mix the NiFeCoWMo / CW obtained above with 1.5 g of NaH 2PO 2 ⋅H 2 O were placed downstream and upstream of the tube furnace. Then, o C min -1 The tube furnace is heated from room temperature to 400 o C, and keep it warm for 4 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0037] Example 4 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 300 o C for 0.5 h, and the heating rate was 1 o C min -1 , and then heated to 1000 o C carbonization for 4 h, heating rate of 3 o C min -1 , obtaining carbonized wood (CW); Step 2: 4 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 0.25 mmol FeCl 3 , 0.25 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 0.25 mmol Na 2 WO 4 ·2H 2 O and 0.25 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was transferred into a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 180 o After cooling to room temperature naturally, the product was washed with water and ethanol three times and heated at 60 oNiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0038] Step 3: Mix the NiFeCoWMo / CW obtained above with 0.5 g of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1 The tube furnace was heated from room temperature to 350 o C, and keep it warm for 2 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0039] Example 5 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction and soak them in 1 M hydrochloric acid for 1 h to remove impurities. Then, wash the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 260 o C for 2 h, with a heating rate of 2 o C min -1 , and then heated to 1000 o C carbonization for 2 h, heating rate 5 o C min -1 , obtaining carbonized wood (CW); Step 2: 1 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 2 mmol FeCl 3 , 0.5 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 0.5 mmol Na 2 WO 4 ·2H 2 O and 1 mmol Na 2 MoO 4 ·2H 2O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was then transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 160 o After cooling to room temperature, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0040] Step 3: Mix the NiFeCoWMo / CW obtained above with 1 g of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1 The tube furnace was heated from room temperature to 500 o C, and keep it warm for 2 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0041] Example 6 The present invention provides a method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, which specifically comprises the following steps: Step 1: Cut the natural poplar wood into 5*5*0.3 cm slices perpendicular to the growth direction, soak them in 1 M hydrochloric acid for 1 h to remove impurities, and then rinse the slices repeatedly with deionized water and anhydrous ethanol. o C vacuum drying for 8 h and finally at 260 o C for 1 h, with a heating rate of 2 o C min -1 , and then heated to 900°C in a nitrogen atmosphere. o C carbonization for 3 h, heating rate 5 o C min -1 , and obtain carbonized wood (CW). ; Step 2: 1 mmol Ni(NO 3 ) 2 ⋅6H 2 O, 1 mmol FeCl 3 , 1 mmol Co(NO 3 ) 2 6H 2 O and 5 mmol citric acid were dissolved in a mixed solvent of 10 mL deionized water and 10 mL anhydrous ethanol and stirred for 20 minutes to obtain solution A; 1 mmol Na 2 WO 4·2H 2 O and 1 mmol Na 2 MoO 4 ·2H 2 O was dissolved in 15 mL of deionized water and stirred for 20 minutes to form solution B. Solution B was slowly added to solution A and magnetically stirred for 20 minutes. Then 8 mmol of hexamethylenetetramine was added and magnetically stirred for 20 minutes. The solution was then transferred to a 50 mL Teflon-lined stainless steel reactor. Finally, a piece of CW was immersed in the solution and heated at 160 o After cooling to room temperature, the product was washed with water and ethanol three times and heated at 60 o NiFeCoWMo / CW was obtained by vacuum drying at C for 15 h.

[0042] Step 3: Mix the NiFeCoWMo / CW obtained above with a certain amount of NaH 2 PO 2 ⋅H 2 O are placed downstream and upstream of the tube furnace respectively. Then, o C min -1 The tube furnace was heated from room temperature to 450 o C, and keep it warm for 2 h. The tube furnace was cooled to room temperature to obtain NiFeCoWMoP / CW.

[0043] from Figure 1a It can be seen that the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst maintains the low-curvature vertical microchannels of the carbonized wood.

[0044] from Figure 1b It can be seen that the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst has rich pore structure and hierarchical structure.

[0045] from Figure 1c It can be seen that the carbonized wood-loaded high entropy phosphide nanosheet composite electrocatalyst has a nanosheet array structure.

[0046] from Figure 2 It can be seen that the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst is based on carbonized wood and has the crystal structure of phosphide.

[0047] from Figure 3 It can be seen that all samples have a -1 and 1582 cm -1 The D-band and G-band are shown, and the intensity ratios of CW, NiFeCoWMo / CW and NiFeCoWMoP / CW (I D / I G) are 0.87, 0.84 and 1.02, respectively, indicating that the defects of the carbon substrate are getting larger and larger, which is beneficial to the improvement of the electrocatalytic activity.

[0048] from Figure 4 It can be seen that the samples contain abundant micropores, and the specific surface area increases from 582.67 m 2 g -1 Down to 319.48 m of NiFeCoWMo / CW 2 g -1 , NiFeCoWMoP / CW 498.47 m 2 g -1 , indicating that CW provides abundant specific surface area.

[0049] from Figure 5 It can be seen that the electrons of elements such as Ni 2p, Fe 2p, Co 2p, w4f, Mo 3d, P 2p, and C 1s of NiFeCoWMoP / CW can be easily distinguished at 870, 720, 795, 36, 234, 134, and 284 eV, respectively, indicating the successful synthesis of carbonized wood-supported high-entropy phosphide nanosheets composite electrocatalyst.

[0050] Figure 6 The hydrogen evolution polarization curve of the carbonized wood-supported high entropy phosphide nanosheet composite electrocatalyst and Pt / C obtained in Example 2 was measured in 1M KOH in a three-electrode system. Figure 6 It can be seen that the current density reaches 100 mA cm -2 When the overpotential of carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst is 0.054 W, the overpotential required for the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst is only 151 mV, while that of Pt is 125 mV. It can be seen that the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst exhibits HER performance close to that of Pt.

[0051] Figure 7 The carbonized wood-loaded high entropy phosphide nanosheet composite electrocatalyst and RuO 2 In the three-electrode system, the oxygen evolution polarization curve measured in 1M KOH is Figure 7 It can be seen that the current density reaches 100 mA cm -2 When carbonized wood-supported high entropy phosphide nanosheets composite electrocatalyst requires an overpotential of only 1.55 V, while RuO 2 It takes 1.677 V, which shows that the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst performs better than RuO 2 The (RuO2) OER performance, Figure 8In the case of a 1M KOH solution, oxygen evolution and hydrogen evolution occurred simultaneously, and the electrolytic cell reached 100 mA / cm 2 The overpotential at 1.746 V is 1.746 V. When the electrolyte is a mixed solution of KOH and glucose (KOH concentration is 1 M, glucose is 50 mM), glucose is oxidized at the anode to avoid the generation of oxygen at the anode. The electrolytic cell reaches 100 mA / cm 2 The overpotential at each of the carbonized wood and high entropy phosphide nanosheet composite electrocatalysts is 1.534 V, which becomes an organic acid and avoids the danger of mixing oxygen and hydrogen. It can be seen that the carbonized wood-loaded high entropy phosphide nanosheet composite electrocatalyst reduces the external potential required for water electrolysis, exhibits excellent glucose electrocatalytic coupling hydrogen production performance, improves the efficiency of water electrolysis to prepare high-purity hydrogen, and is superior to the traditional water electrolysis hydrogen production performance.

Claims

1. A method for preparing a carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst, characterized in that: The following steps are involved: S1, using deionized water as solvent, adding hexamethylenetetramine to a mixed system of Ni(NO3)2⋅6H2O, citric acid, FeCl3, Co(NO3)2·6H2O, Na2WO4·2H2O and Na2MoO4·2H2O and mixing them evenly, the molar ratio of the total amount of Ni(NO3)2⋅6H2O, Co(NO3)2·6H2O, Na2WO4·2H2O, FeCl3 and Na2MoO4·2H2O to citric acid is 1:1, to obtain a mixed system; S2, immerse the carbonized wood into the mixed system and heat it at 140~180 o C, and the obtained product is washed and dried to obtain a carbonized wood-supported high-entropy phosphide nanosheet precursor; S3, carbonized wood-supported high entropy phosphide nanosheet precursor and phosphorus source were heated to 300-600 o C, the ratio of phosphorus source to citric acid in S1 was (0.5~1.5) g: 5 mmol, and the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst was obtained.

2. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 1, characterized in that: S1: Ni(NO3)2·6H2O, FeCl3, Co(NO3)2·6H2O and citric acid are dissolved in a mixed solvent of deionized water and anhydrous ethanol in sequence to obtain solution A; Dissolve Na2WO4·2H2O and Na2MoO4·2H2O in deionized water to obtain solution B; Solution B was added to solution A and magnetically stirred for 15 to 25 min, and then hexamethylenetetramine was added to obtain a mixed system.

3. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 2, characterized in that: The molar ratio of Ni(NO3)2⋅6H2O, FeCl3, Co(NO3)2·6H2O, Na2WO4·2H2O and Na2MoO4·2H2O is (0.25~4):(0.25~4):(0.25~4):(0.25~4), the molar ratio of hexamethylenetetramine and citric acid is 8:5, and the volume ratio of deionized water and anhydrous ethanol in solution A is 1:

1.

4. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 1, characterized in that: The carbonized wood described in S2 is obtained by the following process: The wood pieces were soaked in 0.85-1.15 M hydrochloric acid for 55-65 min, washed with deionized water and anhydrous ethanol, and dried. o The first carbonization was carried out at 0.5-2 h under 400 °C and finally heated to 800-1000 °C in an oxygen-free atmosphere. o C and then carbonized for a second time for 2-4 h to obtain carbonized wood.

5. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 4, characterized in that: The heating rate during the first carbonization is 1~3 o C min -1 The heating rate during the second carbonization is 3~6 o Cmin -1 .

6. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 5, characterized in that: S2 immerses the carbonized wood into the mixed system and heats it at 140~180 o C for 8 to 16 h.

7. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 1, characterized in that: S2 The product was washed with water and ethanol in turn at 55-65 o C and vacuum dried for 12 to 18 h to obtain a carbonized wood-supported high entropy phosphide nanosheet precursor.

8. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 1, characterized in that: S3 The phosphorus source is NaH2PO2⋅H2O. S3 places the carbonized wood-loaded high entropy phosphide nanosheet precursor and NaH2PO2⋅H2O in the downstream and upstream of the tube furnace respectively, and then heats the tube furnace at 300-600 o C for 1-3 h to obtain the carbonized wood-loaded high-entropy phosphide nanosheet composite electrocatalyst.

9. The method for preparing the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to claim 8, characterized in that: S3 2~4 o C min -1 The carbonized wood-supported high entropy phosphide nanosheet precursor and NaH2PO2⋅H2O were heated from room temperature to 300-600 o C, and then keep warm at the above temperature.

10. A carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst obtained by the preparation method of the carbonized wood-supported high-entropy phosphide nanosheet composite electrocatalyst according to any one of claims 1 to 9.